Stress testing a quasi-market : Unintended consequences of the Swedish school voucher system - Bergh, Andreas; Wernberg, Joakim (Scandinavian Journal of Public Administration, 2025)
Quasi-markets are increasingly used in public service provision, yet they remain highly contested. This paper develops a conceptual framework grounded in economic theory to examine how quasi-markets differ from traditional markets along five key dimensions: (1) revenues, costs, and profits, (2) the matching of supply and demand, (3) competition, (4) structural change, and (5) rent-seeking. Assuming profit-maximizing behavior, we stress-test the quasi-market model to explore how these structural differences shape incentives and influence outcomes. Applying the framework to Sweden’s school voucher system, we show that specific design features have led to unintended consequences that undermine service quality and conflict with the reform’s stated policy goals.